Keratuan Adat Menangsi: Sejarah, Sistem Pemerintahan dan Pelestarian Nilai Budaya Masyarakat Lampung Saibatin di Lampung Selatan - Berchah Pitoewas; Abdul Halim; Martines Sabiliun Muttaqina; Siti Musaroh Maydiana Alpa; Adinda Armilia Putri; Dewi Rahayu; Adelia Novitasari; Bagus Permana (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The purpose of this study is to explore the history of the Ratu Menangsi clan in South Lampung. The method used in this research is a historical approach with data collection techniques through interviews and document studies. Based on the research findings, the Ratu Menangsi clan is the oldest clan in South Lampung. The establishment of the Ratu Menangsi clan began with the fall of the Balaw Kingdom in the mid-16th century, specifically around the year 1554. After the collapse, the descendants of Ratu Balaw, especially Ratu Menangsi, relocated and founded the Menangsi Kingdom, which is estimated to have been established around 1594 in the Kalianda area of South Lampung, with its center of government in Way Andak/Batu Handak/Candi Taman, now known as Taman Baru Village. Historical evidence such as ancient graves, forts, traditional relics, and old records support the existence of the Ratu Menangsi Kingdom as one of the oldest traditional kingdoms in the region.